Pengaruh Karakteristik Pekerjaan dan Motivasi Kerja Terhadap Kepuasan Kerja dan Kinerja Pegawai Negeri Sipil - Emy Fibrianti; Zainal Ilmi; Warsilan Warsilan (RELASI : JURNAL EKONOMI, 2021)
This study aims to analyze and find out several factors that can affect job satisfaction and employee performance, variables used in this study are job characteristics, work motivation, job satisfaction, and employee performance, The sample in this study were employees found in the Samarinda Research and Industrial Standardization Center with a total sample of 49 respondents with the data collection method used to distribute questionnaires. Researchers use SPSS as a tool for processing existing data. The results showed that the variable job characteristics have a positive and significant effect both on the variable of job satisfaction and on employee performance variables, work motivation variables have a positive and significant effect on job satisfaction but do not have a positive and significant effect on employee performance, and for job satisfaction variables has a positive and significant effect on employee performance. Keywords: job characteristics, motivation, job satisfaction, performance